The school social climate of the Industrial Technical Educational Institution Julio Flórez, of Chiquinquirá, Boyacá, Colombia - Umaña, Andry; Herrera, Leidy (Impacto Científico, 2025)
The present study is developed in order to describe the school social climate of the eight headquarters of the Industrial Technician Julio Flórez, in Chiquinquirá, Boyacá, Colombia, during the 2022 and 2023 school years. The type of research was descriptive. The design is field, transectal, contemporary and univariable. For data collection, the school social climate scale by Aron et al., (2012) was used with a Cronbach’s Alpha reliability between 0.63 and 0.89. The population was made up of 76 teachers from the eight locations of the Educational Institution. Data analysis was developed using descriptive statistics, specifically the measure of central tendency, the median, since the data were measured at an ordinal level, and frequency. The results indicated that at the Julio Flórez Technical Educational Institution. Chiquinquirá, Boyacá, Colombia,there is an unrewarding social school climate in which teachers have little interaction with each other, which results in little collaboration and teamwork and causes a continuous manifestation of displeasure and criticism among teachers. there is an unrewarding s cial school climate in which teachers have little interaction with each other, which results in little collaboration and teamwork and causes a continuous manifestation of displeasure and criticism among teachers.